1997
DOI: 10.1128/jb.179.22.6887-6893.1997
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thiamin biosynthetic genes (thiCOGE) and production of symbiotic terminal oxidase cbb3 in Rhizobium etli

Abstract: In this paper we report the cloning and sequence analysis of four genes, located on plasmid pb, which are involved in the synthesis of thiamin in Rhizobium etli (thiC, thiO, thiG, and thiE). Two precursors, 4-methyl-5-(␤-hydroxyethyl)thiazole monophosphate and 4-amino-5-hydroxymethylpyrimidine pyrophosphate, are coupled to form thiamin monophosphate, which is then phosphorylated to make thiamin pyrophosphate. The first open reading frame (ORF) product, of 610 residues, has significant homology (69% identity) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
(78 reference statements)
1
59
0
Order By: Relevance
“…On the other hand, a different role of GO in the formation of the thiazole moiety of thiamine was recently proposed (8); this role requires that the imine product of dehydrogenation of glycine is trapped at the active site of GO with the thiocarboxylate produced by the following enzyme of the metabolic pathway, ThiS. This proposal is also supported by the sequence homology between GO and ThiO, a protein that has been suggested to catalyze this reaction in R. etli (31). This nucleophilic addition may occur before hydrolysis of the imine, which, when it is released from the enzyme, takes place immediately.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…On the other hand, a different role of GO in the formation of the thiazole moiety of thiamine was recently proposed (8); this role requires that the imine product of dehydrogenation of glycine is trapped at the active site of GO with the thiocarboxylate produced by the following enzyme of the metabolic pathway, ThiS. This proposal is also supported by the sequence homology between GO and ThiO, a protein that has been suggested to catalyze this reaction in R. etli (31). This nucleophilic addition may occur before hydrolysis of the imine, which, when it is released from the enzyme, takes place immediately.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, the primary sequence of GO shows a high degree of conservation with the product of thiO gene of Rhizobium etli (23.0% of sequence identity). thiO is the second open reading frame of four genes (thiC, thiO, thiG, and thiE) located on plasmid pb, which are involved in the synthesis of thiamine in R. etli (31). R. etli ThiO protein (a 327-amino acid protein) contains at its N terminus a flavin adenine dinucleotide-binding motif and shares many of the residues involved in the catalytic site of DAAO; it has been also suggested that ThiO may have amino acid oxidase activity (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription start site (tss) of the thiC gene lies 211 bases upstream of thiC start codon. The RNA untranslated leader contains a 38-base sequence, named thi box, that is highly conserved in the upstream region of thi genes of organisms as diverse as E. coli, Synechocystis, Bacillus subtilis, and Mycobacterium tuberculosis (14).In this work, we found by functional analysis of the untranslated RNA leader that repression by thiamin is a posttranscriptional event and that the thi box is an element indispensable for the expression of thiCOGE. We also show that the region surrounding the Shine-Dalgarno (S-D) sequence and the first 443 nt of the coding region participate in the regulation of thiCOGE expression by thiamin.…”
mentioning
confidence: 77%
“…Organisms that are able to synthesize thiamine yet lack thiH (e.g. B. subtilis and Rizobium etli) have thiO, which encodes a glycine oxidase (11,21). The remaining genes involved in thiamine synthesis are more widely conserved (22,23).…”
mentioning
confidence: 99%